Case Report: Novel mutation in CHD4 triggers occult breast cancer with bone metastases - Dong, Hang; Zhao, Jingtong; Zhang, Boyin; Wu, Xiaowen; Liu, Guangyao (Frontiers in Oncology, 2025)
Chromatin domain-binding protein 4 (CHD4), the ATPase core component of the NuRD complex, exerts dual roles in epigenetic regulation—mediating both gene silencing and activation. We report a case of occult breast cancer with extensive bone metastasis harboring a novel somatic truncation mutation in the catalytic SNF2 domain (CHD4 p.Trp736Ter). This mutation, unreported in other cancers to date, abolishes ATPase activity and disrupts NuRD complex assembly. Multimodal analysis (PET/CT, biomarkers, pathology) confirmed the case as luminal-A subtype and revealed a significant response to endocrine therapy. We hypothesize that this CHD4 mutation may alter the protein’s dual regulatory balance, particularly enhancing its potential gene-activating functions, and propose that impaired chromatin remodeling driven by such mutations is associated with metastatic progression of breast cancer.